2024
DOI: 10.1007/s00395-024-01034-4
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, cancer, and the cardiovascular system: clinical effects and mechanistic insights

Simon Wernhart,
Tienush Rassaf

Abstract: Cardiovascular diseases and cancer are the leading causes of death in the Western world and share common risk factors. Reduced cardiorespiratory fitness (CRF) is a major determinant of cardiovascular morbidity and cancer survival. In this review we discuss cancer- induced disturbances of parenchymal, cellular, and mitochondrial function, which limit CRF and may be antagonized and attenuated through exercise training. We show the impact of CRF on cancer survival and its attenuating effects on cardiotoxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 221 publications
0
4
0
Order By: Relevance
“…This finding underscores the importance of assessment and management of pre‐existing CVD risk factors including through lifestyle modifications such as increased physical activity, exercise, weight management, healthy diet and smoking cessation in order to reduce CVD risk. 44 , 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…This finding underscores the importance of assessment and management of pre‐existing CVD risk factors including through lifestyle modifications such as increased physical activity, exercise, weight management, healthy diet and smoking cessation in order to reduce CVD risk. 44 , 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Professional support in cancer rehabilitation is of pivotal importance as structured and personalized exercise rehabilitation training in breast cancer survivors reduces fatigue and fatigue-related biomarkers [ 87 ], and can also improve social and physical function [ 88 ]. Taken together, evidence for the beneficial effects of exercise on patients’ well-being and CRF have been demonstrated across the whole temporal continuum of cancer treatment and should induce integration of exercise as a main pillar of standard-cancer therapy [ 89 ]. Future trials will also provide more insights on the effects of structured, individualized exercise to improve quality of life and fatigue in more advanced cancer stages, such as metastatic breast cancer [ 90 ].…”
Section: Exercise Interventions In Cancer Patientsmentioning
confidence: 99%
“…Resistance training (RT), as a measure to reduce or even reverse muscle wasting, is recommended in addition to endurance training to improve CRF by current guidelines of sports cardiology and cardio-oncology [ 8 , 94 ] as it improves skeletal muscle and mitochondrial respiration [ 95 ]. Assessment of muscle strength in cancer patients is usually performed by measuring handgrip strength [ 96 ], and RT intensity to establish training prescriptions should be identified by the one repetition maximum (1 RPM) [ 89 , 94 ]. A meta-analysis of randomized trials of RT during and after chemotherapy in cancer survivors demonstrated the most effective increase of muscle strength at intensities below 75% of 1 RPM [ 97 ] and provides evidence for a safe integration of RT into training of cancer patients.…”
Section: Exercise Interventions In Cancer Patientsmentioning
confidence: 99%
See 2 more Smart Citations